PENGARUH TERAPI BUTTERFLY HUG TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III NULLIPARA DI PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU - Anita Syarifah; Putri Lara Dygta (Ensiklopedia of Journal, 2026)
Anxiety in third-trimester pregnant women, especially nulliparous women, is a common psychological condition that occurs prior to childbirth and can have negative effects on both the mother and the fetus. One non-pharmacological intervention that can be used to reduce anxiety is Butterfly Hug therapy, a bilateral stimulation technique that aims to calm the nervous system and promote relaxation. The purpose of this study was to determine the effect of Butterfly Hug therapy on anxiety levels in nulliparous pregnant women in their third trimester at the Payung Sekaki Community Health Center in Pekanbaru City. This study used a quantitative design with a pre-experimental one-group pretest–posttest approach. The study was conducted from December 17 to 21, 2025. The population in this study consisted of 20 nulliparous pregnant women in their third trimester, with a total sampling technique used for sampling. Data collection was conducted using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis was performed using univariate and bivariate analysis with a paired t-test. The results showed a decrease in anxiety levels among nulliparous pregnant women in their third trimester after receiving Butterfly Hug therapy, with a statistical test result of p-value = 0.001 ( 0.05). The conclusion of this study is that Butterfly Hug therapy has a significant effect on anxiety levels among nulliparous pregnant women in their third trimester at the Payung Sekaki Community Health Center in Pekanbaru City. Butterfly Hug therapy is expected to be used as a non-pharmacological nursing intervention that is easy, safe, and can be done independently to help reduce anxiety in pregnant women approaching childbirth. Keywords: Butterfly Hug therapy, anxiety, third trimester pregnant women, nulliparous women